The teacher training politics as support structures for the work of teaching - Gonzalo Martin Gutierrez; Lucia Beltramino (Ministerio de Educación, Dirección General de Educación Superior, 2017)
In this article, we propose to analyze from a historical perspective, the policies of teacher training in exercise as part of support to the work of teaching. For this we focus in the discussion on the hypothesis of its centrality in explanations on the quality of educational systems, the assumptions of deficit on which they have traditionally 87 been structured and the need to advance in perspectives that depart from questioning about what they do know and can do in the school the teachers. Finally we propose the notion of "shared training" to develop device conceived as areas of meeting between knowledge, needs, expectations, and experiences built in the different areas of the educational system.